Thyroid Autoimmunity and Behçet’s Disease: Is There a Significant Association? - Filiz Cebeci; Nahide Onsun; Ayşe Pekdemir; Ahmet R. Uras; Kadir Kayataş (The Scientific World Journal)
Background. Behcet’s disease (BD) could be regarded as an autoimmune disease in many aspects. Autoimmune thyroid disease (ATD) is frequently accompanied by other various autoimmune diseases. Nevertheless, there is not still enough data showing the association between BD and ATD. In addition, no controlled study is present in the PubMed, which evaluates thyroidal autoimmunity using antithyroid peroxidase antibody in a large series of patients with BD. Methods. We aimed to investigate the frequency of ATD in patients with BD. The study included 124 patients with BD and 99 age- and sex-matched healthy volunteers. Results. Autoimmune thyroiditis was noted in 21 cases (16.9%) with BD. In the control group, 22 cases (22.22%) were diagnosed as autoimmune thyroiditis. There was no difference between the groups in respect to thyroid autoantibodies (). There were no statistically significant differences between baseline TSH levels of the BD patients and of the controls (). Statistically, the mean serum free T4 levels of the patients with BD were higher than those of the controls (). Conclusions. No association could be found between BD and ATD. Therefore, it is not of significance to investigate thyroid autoimmunity in BD.